Serum Low-Density Lipoprotein Cholesterol Levels are Associated with Relapse in Neuromyelitis Optica Spectrum Disorder - Ding J; Chen FP; Song YY; Li HY; Ai XW; Chen Y; Han L; Zhou XJ; Zhu DS; Guan YT (Dove Medical Press, 2024)
Jie Ding,1,* Fu-Ping Chen,1,* Ya-Ying Song,1,* Hong-Yan Li,1 Xi-Wen Ai,1 Yi Chen,1 Lu Han,1 Xia-Jun Zhou,1 De-Sheng Zhu,1 Yang-Tai Guan1,2 1Department of Neurology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200127, People's Republic of China; 2Department of Neurology, Pu Nan Branch of Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this work Correspondence : Yang-Tai Guan; De-Sheng ZhuDepartment of Neurology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China, Tel +86-13386271865; +86-13564719779, Fax +86-21-68383482, Email yangtaiguan@sina.com; deshengzhu2008@sina.comBackground: The relationship between serum low-density lipoprotein cholesterol (LDL-C) and the risk of relapse in neuromyelitis optica spectrum disorder (NMOSD) remains uncertain. We aimed to examine the association between serum LDL-C level and relapse in NMOSD patients.Methods: We conducted an analysis of the prospective observational NMOSD cohort study with consecutive 184 hospitalized NMOSD patients from department of neurology. Blood samples were collected to measure LDL-C level upon admission. Primary and relapse were evaluated during hospitalization. The relationship between serum LDL-C level and relapse were analyzed by linear curve fitting analyses. Crude and adjusted odds ratios (OR) of LDL-C for relapse with 95% confidence intervals were analyzed using multiple logistic regression models. ROC curve analysis was used to identify the target lipid-lowering value of LDL-C and the probability of relapse was evaluated by the Kaplan-Meier Plot.Results: Over a mean disease course of 100± 87 days, 59.24% (n=109) participants developed relapse with higher LDL-C than the primary group (n=75) (p< 0.001). Adjusted smoothed plots suggested that there were linear relationships between serum LDL-C level and relapse (p< 0.001). The OR (95% CI) between serum LDL-C level and relapse were 2.67 (1.76- 4.04, p< 0.001), and 2.38 (1.48- 3.83, p< 0.001) respectively in NMOSD patients before and after adjusting for potential confounders. The target LDL-C lowering values were 2.795 mmol/L with potential benefits to prevent relapse in NMOSD.Conclusion: In this sample of NMOSD patients, we found that the elevated serum LDL-C was independently and positively associated with the relapse, and serum LDL-C should be well-controlled to prevent the relapse of NMOSD.Keywords: neuromyelitis optica spectrum disorder, NMOSD, low-density lipoprotein cholesterol, relapse, multivariate analysis